+0  
 
0
131
1
avatar

3x(-2)

Guest Jul 1, 2017
Sort: 

1+0 Answers

 #1
avatar+91235 
+1

3x(-2)

 

depends what you mean...

 

\(3\times (-2)=-6\\ 3x\times (-2)=-6x\\ 3x^{-2}=\frac{3}{x^2}\\ (3x)^{-2}=\frac{1}{9x^2} \)

Melody  Jul 2, 2017

6 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details